CONSUMER CONFUSION AND ITS IMPACT ON DECISION MAKING AMONG FEMALE CONSUMERS IN INDONESIA’S ONLINE COSMETICS AND PERSONAL CARE INDUSTRY - Marshanda Tristandinata (Journal of Social and Economics Research, 2024)
This study examines consumer confusion and its impact on decision-making among female consumers in Indonesia's online cosmetics and personal care industry. With the rise of online shopping due to its convenience and extensive product information, consumer confusion—defined as the inability to correctly interpret various aspects of product information—has become a significant issue. A mixed-method approach was used, combining quantitative surveys and qualitative interviews. Data was collected through an online survey and analyzed using PLS-SEM, followed by semi-structured interviews that were manually coded through open, axial, and selective coding. The findings reveal that informational sources—overload, similarity, and ambiguity positively impact overall consumer confusion. Additionally, utilitarian decision-makers show higher levels of confusion compared to hedonic decision-makers. Previous brand experience was found to mitigate the negative effects of overload and ambiguity confusion on decision quality and enhance decision quality in the case of similarity confusion. Furthermore, overload and ambiguity confusion negatively impacts decision quality, whereas similarity confusion shows a positive impact. Finally, all informational sources of confusion positively impact decision postponement and cognitive dissonance. This study extends existing knowledge in marketing and consumer behavior, particularly regarding consumer confusion in the cosmetics sector. It offers practical insights for companies and brand managers to develop strategies that reduce consumer confusion, such as simplifying decision-making processes, providing clear product information, and leveraging previous brand experiences. These strategies aim to enhance decision quality, reduce decision postponement, and mitigate cognitive dissonance among consumers. Finally, the study suggests directions for future research in consumer confusion.